2022
DOI: 10.3390/healthcare10112203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Interventions in the Elderly with Anxiety, Depression, and Low Social Support: A Clinical Multicentre Randomised Trial

Abstract: The percentage of older people is increasing worldwide. Loneliness and anxious–depressive states are emerging health conditions in this population group, and these conditions give rise to higher morbidity and mortality. Physical activity (PA) and social relationships have been linked to physical and mental health. The objective of this study was to evaluate whether a 4-month programme of moderate PA in a group would improve the emotional state, levels of social support, and quality of life in a sample of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…46,47 In a study by Ruiz-Comell et al, it was discovered that participating in group walking twice a week for 4 months significantly reduced anxiety among the elderly, with a remarkable 45% decrease. 48 Hence, it is advisable for the elderly to incorporate exercise into their daily routines, with walking being an affordable, economical, and feasible option for most of them. Additionally, engaging in stretching, resistance, and balance exercises according to relevant guidelines offers numerous advantages for the elderly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 In a study by Ruiz-Comell et al, it was discovered that participating in group walking twice a week for 4 months significantly reduced anxiety among the elderly, with a remarkable 45% decrease. 48 Hence, it is advisable for the elderly to incorporate exercise into their daily routines, with walking being an affordable, economical, and feasible option for most of them. Additionally, engaging in stretching, resistance, and balance exercises according to relevant guidelines offers numerous advantages for the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Engaging in physical activity, increasing social interactions, and fostering an active lifestyle can yield several benefits, including enhanced self‐esteem, increased empowerment, reduced mental stress, improved physical and mental health, boosted immunity, and redirection of attention away from anxiety‐inducing stimuli 46,47 . In a study by Ruiz‐Comell et al ., it was discovered that participating in group walking twice a week for 4 months significantly reduced anxiety among the elderly, with a remarkable 45% decrease 48 . Hence, it is advisable for the elderly to incorporate exercise into their daily routines, with walking being an affordable, economical, and feasible option for most of them.…”
Section: Discussionmentioning
confidence: 99%
“…This is because engaging in physical activity is a key strategy for overcoming negative emotions like anxiety, depression, and loneliness, and social support is typically used as a gage for older adults’ quality of life and overall wellbeing ( Liu et al, 2022 ). The results of a four-month clinical trial show that elderly people who are depressed, nervous, or have little social support can benefit from physical activity in terms of their emotional condition, degree of social support, and overall quality of life ( Ruiz-Comellas et al, 2022 ). A comprehensive review also found that socially supported older people were more likely to actively participate in amateur sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…The current survey found 26% no anxiety, 35% mild, 21% moderate, and 18% severe. PA is linked to physical and mental health, reducing anxiety [2]. A growing body of work supports the effectiveness of both aerobic and resistance exercise paradigms in the treatment of anxiety [37].…”
Section: Discussionmentioning
confidence: 99%
“…The burden of disease among older people is high and tends to increase, as one in five people will be over 60 years old, according to projections by the World Health Organization (WHO) [1]. The percentage of older people is increasing worldwide, and "anxiety-depressive" states are emerging health conditions in this population group, increasing both morbidity and mortality [2]. With the growth of the older people population around the world, promoting their health by helping them to achieve a better life, and at the same time reducing the burden on care services, has been the action of academics and professionals around the world, governments, international organizations [3].…”
Section: Introductionmentioning
confidence: 99%